2022
DOI: 10.1039/d1ta08709f
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogels with highly concentrated salt solution as electrolytes for solid-state supercapacitors with a suppressed self-discharge rate

Abstract: Solid-state supercapacitors (SSSCs) using hydrogel electrolytes have attracted great interest in recent years due to their potential for powering flexible and wearable electronics. But the application of SSSCs has been...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…This reduction is attributed to electron transfer impedance during electrolysis on account of increased formation of hydration clusters and reduced availability of free water molecules. Shi et al (2021) observed that the float currents reduced by 27 and 10.5 times at 0.8 and 1.6 V, respectively, when the concentration of LiCl increased from 1 to 14 M. Similar results were reported by Avireddy et al (2019) and Shi et al (2022).…”
Section: Addition Of Surfactantssupporting
confidence: 79%
“…This reduction is attributed to electron transfer impedance during electrolysis on account of increased formation of hydration clusters and reduced availability of free water molecules. Shi et al (2021) observed that the float currents reduced by 27 and 10.5 times at 0.8 and 1.6 V, respectively, when the concentration of LiCl increased from 1 to 14 M. Similar results were reported by Avireddy et al (2019) and Shi et al (2022).…”
Section: Addition Of Surfactantssupporting
confidence: 79%
“…There have been approaches utilizing transformers, mechanical/electronic switches, and more recently, strategies for coupling charge pump circuits to BUCK circuits [52]. It is also possible to combine supercapacitors to store the energy collected by TENGs [53]. The utilization of energy management strategies for hydrogel-based TENGs is a perspective to drive their improvement.…”
Section: Hydrogel-based Tengs 21 Hydrogel-based Tengs For Energy Harv...mentioning
confidence: 99%
“…It was worth mentioning that most hydrogel electrolyte based supercapacitor suffers from poor rate capability. 25,43,63 The outstanding rate performance in the supercapacitor with HE-NaClO 4 -15 is mainly attributed to the low R s with the iondiffusion rate in hydrogel electrolytes and low R ct with fast charge transfer between active electrode materials and the electrolyte. Comparing the electrochemical properties of three kinds of flexible supercapacitors, it is found that the CV curve of the supercapacitor assembled with HE-NaClO 4 -15 hydrogel electrolyte has the largest integrated area at a scanning speed of 100 mV s −1 (Figure S11a), which further verifies that the supercapacitor assembled with HE-NaClO 4 -15 hydrogel electrolyte has excellent rate performance.…”
Section: Rate Performances Of Supercapacitors Assembled With High-sal...mentioning
confidence: 99%